Review Literatur : Studi Tingkat Pemahaman Education Sustainable Development (ESD) pada Siswa SMA - Karmana, I Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Indonesia is a developing country that is being intensively carrying out development. However, in carrying out development, there are positive and negative impacts. One of the negative impacts is the impact on the environment. For decades, the environment in Indonesia has become increasingly alarming, this is where the concept of sustainable development is very important to be applied so that development runs well without compromising the interests of the environment itself. This study aims to determine the characteristics and how to implement Education Sustainable Development (ESD) in Biology learning with the literature review method, namely a literature search both nationally and internationally which is carried out by reviewing thesis and journals. Based on the journal reviews that have been carried out, the understanding of Education Sustainable Development (ESD) at the high school level has increased through variations in learning models and media.